A produção da cerâmica vermelha e sua relação com a saúde do trabalhador e os impactos ambientais no município de Parelhas\RN - Dantas, Flávia Priscila (2020)
The red ceramic industry is considered one of the most profitable economic activities in the semi-arid region of the State of Rio Grande do Norte. However, at the same time that this red ceramic extraction activity generates jobs and income for the local population, it is also responsible for the unsanitary conditions in the production line and for the advance of the desertification process in the region. In this sense, the present work had as main objective to understand the ceramic production process in two companies in the municipality of Parelhas / RN and its relation with the working environment conditions and environmental impacts in the region. The research verified how labor activities are carried out in the production line of red ceramics and observed the conditions of unhealthy and environmental degradation generated by this economic activity in the study area. For the evaluation of working conditions in the ceramic production line, the Rapid Entire Body Assecement (REBA) postural analysis method was used for ergonomics and the RTD (Thermal Discomfort Index) to evaluate the thermal comfort conditions in the working environment. with thermal sensation bands adapted by Neres, Santos and Carvalho (2015) for semiarid regions. For the identification and characterization of environmental impacts in locu, the adapted Leopold Matrix (1971) was used, followed by the photographic record in the field. Then, the environmental impacts were characterized and classified according to the environmental systems impacted in the region. The research results show that the workers of the two ceramic companies investigated are subjected to unhealthy conditions in the production line and low wages, and that there is no social division of labor between men and women in the production process. It was also found that ceramic activities enhance the installation of the desertification process through environmental impacts on the physical and biological environment. Each step in the ceramic production line generates a series of environmental impacts with adverse consequences for the region. Thus, it is concluded that the investigated companies operate in an unsustainable manner generating a series of socioenvironmental impacts in the region, and that local workers are subjected to unhealthy working conditions in the production area of the companies investigated in the study area. The strengthening of environmental inspection and the application of environmental and labor laws become urgent measures in the study area to guarantee local environmental sustainability.